EMERGING TRENDS IN POLICY AUTOMATION FOR CLOUD GOVERNANCE: A TECHNICAL ANALYSIS - Vinay Reddy Male (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This technical article examines the transformative impact of policy automation on cloud governance, focusing on how organizations leverage artificial intelligence and machine learning to enhance security and compliance management. The article explores core components of policy automation, implementation examples across major cloud platforms, benefits, challenges, and future developments. The article further demonstrates that automated policy enforcement significantly improves operational efficiency, reduces security incidents, and streamlines compliance management across complex multi-cloud environments. While highlighting the advantages of automation, the analysis also addresses critical challenges, including configuration risks and the necessity of human oversight, providing insights into balancing automated systems with human expertise for optimal governance outcomes.